Implementation of Health Service Policy Programs to Reduce Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) Through the Strengthening of AMP-SR (Maternal Perinatal Audit Surveillance and Response) in Sidoarjo Regency - Saleh, Rachmad; Sukristyanto, Agus; Handoko, Rudy (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (AKB) are still strategic public health problems in Indonesia, including in Sidoarjo Regency. The local government has implemented health service policies through the strengthening of the Maternal Perinatal Surveillance and Response Audit (AMP-SR) as an effort to accelerate the reduction of AKI and AKB. However, the effectiveness of the implementation of these policies requires an in-depth study to ensure the achievement of policy objectives according to the local context. This study aims to analyze the implementation of health service program policies in the context of reducing AKI and AKB through strengthening AMP-SR in Sidoarjo Regency. This research uses a descriptive qualitative approach with a focus on the policy implementation process, policy actors, and the social and institutional environment that influences the implementation of the program. Data was collected through policy document studies, stakeholder interviews, and field observations. The results of the study show that the implementation of the policy to reduce AKI and AKB in Sidoarjo Regency has been carried out in accordance with Regent Regulation Number 27 of 2020 through the establishment of the Forum for Reducing Maternal and Infant Mortality Rates (Penakib). The main supporting factors include strengthening integrated ANC, optimizing Posyandu, assisting high-risk pregnant women, utilizing health technology, and cross-sector collaboration. However, policy implementation still faces obstacles in the form of uneven community economic empowerment, limited private sector support, and low public awareness related to maternal and child health. Overall, strengthening AMP-SR plays an important role in supporting the effectiveness of the implementation of policies to reduce AKI and AKB, but requires strengthening collaborative aspects and empowering communities so that the results are more sustainable.